(untitled) (Archives of Pediatrics of Uruguay, 2023)
Introduction: in March 2021, there was a peak incidence of COVID-19 and an increase in pediatric infections in Uruguay. Objective: describe the clinical characteristics, treatment and evolution of a group of children under 15 years of age with SIM-Ped S hospitalized in two health centers. Methodology: descriptive, retrospective study of children hospitalized between 3/1 and 6/31 of 2021 who met the WHO diagnostic criteria for SIM-Ped. Clinical and paraclinical variables, as well as treatment and evolution were analyzed. Results: 12 children were included, median age 7 years (22 months-10 years). Eight of them showed post-infectious complications and 4 of them had complications during the course of the infection. The manifestations were: fever (mean 6 days, range 3-10), digestive symptoms 10 and mucocutaneous 7. Five of them presented a Kawasaki-like disease and 2 of them shock. SARS CoV-2 infection was confirmed by PCR in 6 cases, serology in 4 and antigenic test in 2. Eight of them received treatment in moderate care and 4 of them in intensive care: immunoglobulin 9, corticosteroids 11, heparin 7 and acetylsalicylic acid 7. Two of them presented dilated arteries coronary , valvular alterations 2, decreased LVEF 2 and pericardial effusion 2. All progressed favorably. Conclusions: in these centers, the first cases of SIMS-Ped S coincided with the peak incidence of COVID-19 in the country. Post-infectious forms predominated in schoolchildren who showed digestive manifestations. This study may contribute to the recognition of this entity and to the adaptation of national management algorithms.